2020
DOI: 10.1002/cpp.2477
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic stress symptoms of health care workers during the corona virus disease 2019

Abstract: Corona virus disease 2019 (COVID-19) outbreak has attracted worldwide attention.The COVID-19 outbreak is unique in its rapid transmission and results in heavy stress for the front-line health care workers (HCWs). The current study aimed to exam posttraumatic stress symptoms (PTSSs) of HCWs fighting for the COVID-19 and to evaluate their sleep quality after 1-month stressful suffering. Three hundred seventyseven HCWs working in different provinces of China participated in the survey between February 1 and 5. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
167
4
8

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 186 publications
(197 citation statements)
references
References 44 publications
(39 reference statements)
10
167
4
8
Order By: Relevance
“…Similar to our findings, investigators in China, Italy, and Turkey have reported higher levels of anxiety and depression in female health care providers during the COVID-19 pandemic. 3,[10][11][12][13][14] While investigators in Turkey found that having a child was associated with lower anxiety and depression levels, we did not find a similar protective effect of parenthood or differences in any of the other factors that we examined.…”
Section: Discussioncontrasting
confidence: 89%
“…Similar to our findings, investigators in China, Italy, and Turkey have reported higher levels of anxiety and depression in female health care providers during the COVID-19 pandemic. 3,[10][11][12][13][14] While investigators in Turkey found that having a child was associated with lower anxiety and depression levels, we did not find a similar protective effect of parenthood or differences in any of the other factors that we examined.…”
Section: Discussioncontrasting
confidence: 89%
“…9 Based on previous research, some researchers expect that with increasing deaths and other risk factors leading to psychological trauma, the rates of PTSD may rise above 10% in the current pandemic. 9,11,30 Moral injury in the form of a perceived inability to help the patient may also contribute to the development of PTSD.…”
Section: Post-traumatic Stress Disordermentioning
confidence: 99%
“…The increasing numbers of patients and suspected cases have caused public worry about becoming infected. In addition to health care workers 4 , police o cers are also bravely ghting on the front lines of the epidemic 5 . These police o cers not only face the same risk of infection as the general public, but also suffer from fatigue caused by overtime working and the pressure of responsibility.…”
mentioning
confidence: 99%